2022
DOI: 10.1155/2022/5696686
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Exposure Increases Glucose-6-phosphate Dehydrogenase, Autophagy, Fibrosis, and Senescence in Kidney Cells In Vitro and In Vivo

Abstract: Cigarette smoke (CS) is a risk factor for chronic obstructive pulmonary disease. We attempted to investigate fully the possible effects of CS on kidney cells. We found that the viability of a human kidney proximal tubular epithelial cell line (HK-2 cells) was decreased after treatment with CS extract (CSE). In particular, the effects of CSE at low concentrations did not change the expression of apoptosis and necrosis. Furthermore, CSE increased autophagy- and fibrosis-related proteins in HK-2 cells. Senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…An investigation of the systemic effects of chronic smoking on skin architecture confirmed extensive remodeling of the dermal elastic fiber system [ 200 ]. Liu et al showed that cigarette smoke-induced fibrosis in human kidney cell lines was related to the inhibition of the ROS pathway and the induction of expression of the profibrotic factors CTGF and PAI-1 [ 180 ]. Furthermore, cigarette smoke was confirmed to induce epithelial-to-mesenchymal transition in non–small–cell lung cancer through HDAC-mediated downregulation of E-cadherin, a prognostic factor for lung cancer in smokers [ 181 ].…”
Section: Risk Factors For Pathogenesis Of Peyronie’s Diseasementioning
confidence: 99%
“…An investigation of the systemic effects of chronic smoking on skin architecture confirmed extensive remodeling of the dermal elastic fiber system [ 200 ]. Liu et al showed that cigarette smoke-induced fibrosis in human kidney cell lines was related to the inhibition of the ROS pathway and the induction of expression of the profibrotic factors CTGF and PAI-1 [ 180 ]. Furthermore, cigarette smoke was confirmed to induce epithelial-to-mesenchymal transition in non–small–cell lung cancer through HDAC-mediated downregulation of E-cadherin, a prognostic factor for lung cancer in smokers [ 181 ].…”
Section: Risk Factors For Pathogenesis Of Peyronie’s Diseasementioning
confidence: 99%
“…10 Repeatedly exposed with tobacco toxins can induce intracellular ROS accumulation, resulting in cell senescence, apoptosis, and ultimately tissue destruction. [11][12][13] Autophagy is a self-protective mechanism that maintains intracellular homeostasis in response to various stress conditions, 14,15 which can limit reactive oxygen species (ROS) production by removing oxidized/damaged proteins and bulky organelles that produce ROS such as mitochondria and peroxisomes. Disrupted autophagy was found to increase the intracellular ROS level and aggravate periodontitis.…”
Section: Introductionmentioning
confidence: 99%